The urea and time effect in the fermentation in the soIid state of the fruit s fIour of the bread tree (Artocarpus altilis) (2015)
To evaluate the urea levels inclusion effect and the time on the fermentative and chemical indicators of the flour of fruits of the bread tree, fermented in solid state, was mixed homogeneously, with sulfate of magnesium (0,2%), mineral premix (0,5%) and diluted in distilled water. A totally randomized design was used with factorial arrangement (4x4) with 4 repetitions for treatment to evaluate the effect of the urea (0, 0,5, 1,0 and 1,5%) and four times of fermentation (0, 12, 24 and 48 h).ln the study, as the level of urea is increased, the concentration of ammonia grows the pH, which depends, in smaller or bigger degree, on the organic acids concentration (AGCC and lactic). At the end of the fermentative process there was a decrease in the MS (P <0,001) as the fermentation time passed. The addition of 1,5% of urea produced an increment in the concentration from PB at 24 48 h without difference among them, something similar happened with the PV and the relationship among them (PV:PB)*100 without interaction among the factors in study.At 48 h there was an increase bigger than 2,15 percentage units in the PB with regard to the zero hour. It is concluded that the addition of urea in the fermentation process of the flour from the fruits of the bread tree in solid state, increases the microbial protein synthesis.